The effect of audit adjustments on earnings quality: Evidence from China - Lennox, Clive; Wu, Xi; Zhang, Tianyu (Journal of Accounting and Economics, 2016)
We examine how adjustments to earnings during year-end audits affect measures of earnings quality. There are four key findings. First, audit adjustments cause earnings to become smoother and more persistent. Second, the adjustments result in higher accrual quality. Third, audit adjustments have a larger negative effect on signed accruals than absolute accruals. Fourth, the adjustments do not reduce the discontinuity in the earnings distribution around zero. These findings are of interest to researchers who use earnings properties as proxies for earnings quality and audit quality. However, we caution that our findings for China may not generalize to other countries.